(untitled) (KYAMC Journal, 2024)
Background: Inflammation of the nose and paranasal sinus is a clinical problem frequently encountered in the practice of otolaryngology in our country. Endoscopic sinus surgery is a minimally invasive technique for the evaluation and treatment of inflammatory sinonasal disease. Endoscopic sinus surgery is used to restore sinus ventilation and normal function of sinuses. Objectives: To see the outcome of endoscopic sinus surgery associated with inflammatory sinonasal diseases. Materials and Methods: It is a prospective observational study carried out in ENT &Head Neck Surgery of Shaheed Suhrawardy Medical College Hospital Dhaka from April 2016 to September 2016.Fifty(50) patients were enrolled in this study. Data was collected by Structural Questionnaire. Result: The majority of patients were 21-30years age group. The mean age group was 35.32 years, Male: male-to-female ratio was 1.3:1. The Majority of cases were antrochoanal polyps followed by an ethmoidal polyp, chronic maxillary sinusitis, and fungal rhinosinusitis. The majority of patients came with nasal obstruction and nasal discharge. Polyp was found in the majority of cases. A major complication was found in hemorrhage. Symptomatic improvement was found following endoscopic sinus surgery. KYAMC Journal Volume: 14, No: 04, January 2024: 226-233.